PERAN KADER ANTI PENYALAHGUNAAN NARKOBA BERBASIS PELAJAR OLEH BADAN NARKOTIKA NASIONAL SURABAYA - Devyi Mulia Sari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
BNN is one of the institutions in Indonesia that handle drugs abused problems in the country. The results of BNN survey found that drug abused suspects reached 3.1 million to 3.6 million people in 2008 which was dominated by students. One of BNN Surabaya eff orts in overcoming a drug abusing and illicit drug traffi cking is by forming student-based cadres. The cadres consist of several schools in Surabaya and they are trained to run in accordance with their role. The role of the cadre itself is to become an extension of BNN Surabaya for disseminating the danger of drug abuse in around student circles or peer group. This research was a descriptive research, used case study design. Informants inthis study were P2M BNN Surabaya and some cadres of both female and male students who around at 15–17 years old. Data were collected by interview which contain of explanations by P2M about the formation of cadres and the tasks assigned to the cadres as well as by interview when fi eld off with the cadres. The results showed that the role of cadre in school environment is as Peer Counselor, Peer Educator, and Peer Leadership. Within achieving the success of the role of cadres, it could be seen from health promotion aspect by looking at the level of knowledge, attitude, action and able to communicatewell in order to indicate success in these activities can be achieved.Keywords: cadres, students, drugs abused